Effectiveness of school-based universal social, emotional, and behavioral programs: Do they enhance students' development in the area of skill, behavior, and adjustment? - SKLAD, MARCIN; DIEKSTRA, RENÉ; RITTER, MONIQUE DE; BEN, JEHONATHAN; GRAVESTEIJN, CAROLIEN (Psychology in the schools, 2012)
To answer the question of whether teaching social and emotional skills to foster social–emotional development can help schools extend their role beyond the transfer of knowledge, the authors conducted a meta‐analytical review of 75 recently published studies that reported the effects of universal, school‐based social, emotional, and/or behavioral (SEB) programs. The analyzed interventions had a variety of intended outcomes, but the increase in social skills and decrease in antisocial behavior were most often reported. Although considerable differences in efficacy exist, the analysis demonstrated that overall beneficial effects on all seven major categories of outcomes occurred: social skills, antisocial behavior, substance abuse, positive self‐image, academic achievement, mental health, and prosocial behavior. Generally, immediate effects were stronger than delayed effects, with the exception of substance abuse, which showed a sleeper effect. Limitations of the analysis and moderators of the effectiveness of SEB programs in schools are discussed in the final section of the article.